TERRITORIAL IMAGE MANAGEMENT: DIGITAL STRATEGIES AND IMMERSIVE TECHNOLOGIES FOR THE FOR PROMOTION AND LEADERSHIP (Development Service Industry Management, 2025)
The paper is dedicated to the comprehensive topic of management and imageology, examining them as interconnected spheres of influence in modern society. In the context  of rapid globalization for leadership and urbanization, countries, regions, and cities compete not only for economic advantages, but also for the most valuable resource – human capital: tourists, qualified specialists, students, and innovators. In this regard, so-called "soft factors" come to the fore, such as reputation, cultural attractiveness, and the general impression that the territory makes on the outside world, all of which constitute its image. The Goal of the article is to introduce the concept of territorial image, its key components, and modern tools for its formation, particularly digital and immersive technologies, for the effective promotion of cities, regions, and countries at national and international levels. Territorial image is defined as a holistic, emotionally colored image of the territory (country, region, city), which is formed in the minds of various social groups based on information, personal experience, and stereotypes. A positive  image for a leader becomes a real and extremely important resource of the economy, and a key competitive resource for establishing partnership relations.The study systematizes the main components of the territorial image, which include: natural and geographical characteristics, historical and cultural heritage, socio-demographic and human capital, economic and business climate, the image of authorities and institutions, and informational potential and symbolic capital. Strategic mechanisms for forming the country's international image are considered, particularly state branding. The national brand model relies on six spheres ("Anholt's Hexagon"): exports, governance, culture and heritage, people, tourism, and investment and immigration. Other mechanisms include public diplomacy and coordinated strategic communications. Special attention is paid to the integration of digital strategies for regional promotion. It is highlighted that in the digital era, social networks (Facebook, Instagram, TikTok, YouTube) are powerful tools for visual storytelling and providing instant feedback. Promo-sites and landing pages serve as central information hubs for various target audiences, including investors and potential residents. The use of video content, especially immersive technologies (VR/360° video), creates the effect of full immersion, which is particularly relevant for attracting tourists and investors at the decision-making stage. The role of Artificial Intelligence (AI) is analyzed, which is applied for Big Data analysis, content generation, and providing personalized recommendations to users. The transformation of territorial image under the influence of global crises, including the COVID-19 pandemic and the full-scale military aggression in Ukraine, is investigated. These periods required the swift adaptation of communication strategies and a re-evaluation of values. The full-scale invasion fundamentally changed Ukraine’s international image. Ukraine began to be associated with courage, resilience, and the fight for democratic values. The image of the state leadership, particularly President V.Zelenskyi’s switch to the military style of khaki clothing, became a powerful visual symbol of unity with the people, contributing to the mobilization of international support.
Keywords: Image; Management; Leadership; Territorial image; Place brand; Digital strategies; Immersive technologies; Virtual Reality (VR); Augmented Reality (AR)